Metodologías aplicables a la determinación de velocidad y dirección del flujo de aguas subterráneas mediante trazadores artificiales - calvo, Carlos Sebastián (2017)
The present report, in the frame of the field studies of the Project “Evaluation of the Groundwater Resources of Peru”, methodologies and techniques developed for onsite artificial tracer aided measurements of groundwater flow velocities and flow directions, are presented here. Horizontal flows are computed through labeling of the whole water column which is coated with a holed pipe in its entire length, below the piezometric level. On the other hand, flow directions are found by the aid of a particular radiotracer with adsorption properties in electroplated metals, by monitoring its concentration in terms of radiation count rate at the inside perimeter of the well. Concentration monitoring inside the well, requires the installation of a proper metal net positioned and fixed with a well-known orientation inside the well, prior to the experiment